BMI trajectories among children diagnosed with type 1 diabetes mellitus at a tertiary diabetes center - Al Khalifah, Reem Abdullah; Bawahab, Noor Salem; Wadea, Raghad; Gasim, Hala; Alrashed, Alhanouf; Al-Jelaify, Muneera; Alnassir, Bayan; Saleh, Eman Ragab; Al-Gadi, Iman (Frontiers in Endocrinology, 2025)
ObjectiveThe incidence of type 1 diabetes mellitus (T1DM) has increased worldwide, raising concerns about the intersection between T1DM and the rising prevalence of childhood obesity. This study investigates secular trends in body mass index (BMI) at T1DM diagnosis and its trajectory post-diagnosis, focusing on predictors of obesity persistence.MethodsThis retrospective cohort study was conducted at a tertiary diabetes center in Riyadh, Saudi Arabia, between January 2015 and December 2023. Children under 14 years diagnosed with T1DM at the center were included, while those diagnosed elsewhere or with other diabetes types were excluded. Data included demographics, BMI z-scores based on Saudi and CDC growth charts, HbA1c levels, and clinical presentations like diabetic ketoacidosis (DKA). Linear regression assessed secular trends and predictors of baseline BMI z-scores.ResultsAmong 1160 screened children’s charts, 408(35.17%) children met inclusion criteria. At diagnosis, mean age was 7.87 ± 3.53 years, with 161 (39.5%) presenting with DKA. The mean baseline BMI was 16.06 ± 3.62 kg/m², and BMI z-scores were -0.22 ± 1.65 (Saudi growth references) and -0.87 ± 1.92 (CDC growth references). No significant secular trends in BMI z-scores, gender, or DKA presentation were observed. Of 59(14.46%) children with baseline overweight/obesity, 46 (77.97%) remained overweight/obese at follow-up (p<0.001). The mean BMI z-score increased to 1.14± 1.64 at follow-up, with 113(27.70%) meeting overweight/obesity criteria.ConclusionOverweight/obesity at diagnosis with T1DM persists at follow-up. Addressing obesity at T1DM diagnosis is crucial for mitigating its long-term metabolic impact. Future research should target interventions addressing lifestyle factors contributing to obesity in children with T1DM.